2011
DOI: 10.1007/s11069-011-0057-5
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic radiation influence on the physiological state of aviators

Abstract: Aviation personnel exposure to cosmic radiation and its biological effects has been an interesting subject for research over the last decade. In this study, scientific groups from Greece, Slovakia, and Bulgaria collaborated in order to examine the potential effects of cosmic radiation on the cardiovascular functionality of a group of Slovak aviators. Specifically, daily data concerning mean values of arterial diastolic and systolic blood pressure, which were registered during the medical examinations of the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Furthermore, geomagnetic storms and FDs of the CRI result in variations of the human physiological parameters. More precisely, high GMA and strong CRI decreases were related to HR, RR interval, SP, and DP variations (Papailiou et al 2011 , 2012 ; Mavromichalaki et al 2012 , 2021 ; Galata et al 2017 ), whereas the connection (correlation or anti-correlation) of solar, geomagnetic, and CRI variations to the number of occurrence of different types of cardiac arrhythmias was established in a number of studies (Giannaropoulou et al 2014 ; Mavromichalaki et al 2017 , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, geomagnetic storms and FDs of the CRI result in variations of the human physiological parameters. More precisely, high GMA and strong CRI decreases were related to HR, RR interval, SP, and DP variations (Papailiou et al 2011 , 2012 ; Mavromichalaki et al 2012 , 2021 ; Galata et al 2017 ), whereas the connection (correlation or anti-correlation) of solar, geomagnetic, and CRI variations to the number of occurrence of different types of cardiac arrhythmias was established in a number of studies (Giannaropoulou et al 2014 ; Mavromichalaki et al 2017 , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The statistical methods of analysis of variance (ANOVA, http://www.statisticssolutions.com/manovaanalysis-anova/ ) (Papailiou et al 2012 ; Dimitrova et al 2013 ) and of multiple linear regression analysis were applied, so as to determine the effect of cosmic rays and geomagnetic disturbances on the human physiological parameters (i.e., HR). A univariate analysis was conducted alongside, in order to evaluate the importance of the negative confounding factors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional support for this area of research has been extended by the field of chronobiology in order to examine cycles associated with both biological and epidemiological measures, as well as related space weather variables. In particular, a range of relationships have been revealed between space weather parameters and human cardiovascular activity [16,17] and brain activity [18,19], as well as for a number of diseases including cardio-and cerebrovascular pathologies [20,21]. Of particular relevance for the current research, Zeng et al [21] recently identified strong coperiodicities in patterns of daily mortality due to both cardio-and cerebrovascular diseases in China with a number of heliogeophysical variables including solar and geomagnetic activity, as well as the interplanetary magnetic field.…”
Section: Introductionmentioning
confidence: 99%